PENGARUH PROMOSI DAN HARGA TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA COFFESHOP “FORESHTREE COFFE” DHARMASRAYA - Yogi Rinaldi; Vicky Brama Kumbara; M. Afuan (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2026)
This study aims to determine the extent of the influence of promotion and price on customer loyalty through customer satisfaction as an intervening variable at “Foreshtree Coffee” Dharmasraya. This research employs a quantitative approach, and the sampling technique is based on Ferdinand’s method, as the population size is unknown. A total of 100 respondents were obtained. Data analysis was conducted using SmartPLS 3.0 software. The results of the study are as follows: a) There is a positive and significant effect of promotion on customer satisfaction at Foreshtree Coffee Dharmasraya. b) There is no positive and significant effect of price on customer satisfaction at Foreshtree Coffee Dharmasraya. c) There is a positive and significant effect of promotion on customer loyalty at Foreshtree Coffee Dharmasraya. d) There is a negative and insignificant effect of motivation on customer loyalty at Foreshtree Coffee Dharmasraya. e) There is a positive and insignificant effect of customer satisfaction on customer loyalty at Foreshtree Coffee Dharmasraya. f) Customer satisfaction mediates the relationship between promotion and customer loyalty. g) Customer satisfaction does not mediate the relationship between price and customer loyalty.